ANALISIS CEDERA OLAHRAGA DAN EFEKTIVITAS PENANGANANNYA PADA ATLET BOLAVOLI PUTRI BANK JATIM DI KEJUARAAN LIVOLI 2025 - Syafaatuzzahra, Lailiyah; Januardi, Roy; Rohman, Fatkhur; Adi, Testa (JURNAL ILMU KEOLAHRAGAAN, 2025)
This study aims to identify the types of injuries, treatments, and recovery outcomes of Bank Jatim women’s volleyball athletes during the 2025 Livoli Championship using a qualitative descriptive approach. Fourteen athletes were examined through total sampling, with primary data collected from structured interviews and direct observations, and secondary data from documentation and team records. Results revealed that almost all athletes experienced injuries at various locations, with the knee being most vulnerable (10 athletes), followed by the shoulder (6), wrist and ankle (3 each), as well as back, waist, and heel injuries. Internal factors included lack of warm-up, incorrect technique, and low muscle flexibility, while external factors related to court conditions. Treatments involved RICE, sport massage, physiotherapy, injections, surgery, kinesiotaping, and painkillers, with RICE considered the most effective. Recovery outcomes varied by injury type, but medical and physiotherapy support, along with athlete motivation, ensured optimal recovery and readiness to compete.